Laser Acceleration of Electrons, Protons, and Ions V 2019
DOI: 10.1117/12.2521040
|View full text |Cite
|
Sign up to set email alerts
|

Wakefield excited by ultrashort laser pulses in near-critical density plasmas

Abstract: Laser wakefield acceleration (LWFA) using high repetition rate mJ-class laser systems brings unique opportunities for a broad range of applications. In order to meet the conditions required for the electron acceleration with lasers operating at lower energies, one has to use high density plasmas and ultrashort pulses. In the case of a few-cycle pulse, the dispersion and the carrier envelope phase effects can no longer be neglected. In this work, the properties of the wake waves generated by ultrashort pulse la… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 42 publications
(42 reference statements)
0
3
0
Order By: Relevance
“…Regarding keV-order electron beam generation, previous studies have shown that LWFA at a near critical density (ne/nc ∼ 1) can generate such electrons with high conversion efficiency. [28][29][30] At solid targets, Lei et al proposed a foam cone-in-shell solid target design aiming at optimum hot electron production for laser fusion. 31 They demonstrated that a high-Z low-density novel foam cone-in-shell target enhances laser conversion into hot electrons without increasing the electron temperature (Te = 1.5 MeV) and beam divergence.…”
Section: Articlementioning
confidence: 99%
“…Regarding keV-order electron beam generation, previous studies have shown that LWFA at a near critical density (ne/nc ∼ 1) can generate such electrons with high conversion efficiency. [28][29][30] At solid targets, Lei et al proposed a foam cone-in-shell solid target design aiming at optimum hot electron production for laser fusion. 31 They demonstrated that a high-Z low-density novel foam cone-in-shell target enhances laser conversion into hot electrons without increasing the electron temperature (Te = 1.5 MeV) and beam divergence.…”
Section: Articlementioning
confidence: 99%
“…If the plasma density is near the laser critical density, the typical physics of LWFA transitions into a qualitatively distinct regime where analytic extensions of conventional wakefield physics [27] may become insufficient. Crucially, as n e approaches n c , the group velocity of the laser pulse, given by v g = c √ 1 − n e /n c , approaches zero.…”
Section: Acceleration In the High-density Regimementioning
confidence: 99%
“…Despite LWFA having nearly half a century of history, there has yet to be sufficient exploration of laser-plasma acceleration near the critical density. Valenta et al determined that electron densities of roughly 0.1n c were necessary for high repetition rate, low energy, and short pulse lasers [6]. More recently, Nicks et al further explored how one can achieve bulk acceleration of electrons by exploring the maximum energy achieved for different near-critical densities, laser intensities, and laser pulse widths [4,7].…”
Section: Introductionmentioning
confidence: 99%